Challenges Encountered by BSEd-Mathematics Students in the Implementation of Hybrid Learning in Gordon College - Fruto, Ryan Justin; Felarca, Clarize A.; Aquino, Edison T.; Paguio, Darwin P.; Fastidio, Leby A.; Yap, Katherine D. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study examines the challenges faced by Bachelor in Secondary Education Major in Mathematics students at Gordon College in implementing hybrid learning for the academic year 2022-2023. The research involved 73 students, primarily in their first year, and found that online students face difficulties with math symbol encoding, connectivity, time management, and financial constraints. Onsite students face learning gaps, commuting and access issues, and require additional financial support. The study found no significant difference in challenges based on profile-variables in online mode, but differences exist based on year level and municipality. Recommendations include enhanced technical support, online tool training, time and stress management programs, financial assistance for low-income students, and improved accessibility in onsite mode.